2019
DOI: 10.3389/fgene.2019.00395
|View full text |Cite
|
Sign up to set email alerts
|

Combining Understanding of Immunological Mechanisms and Genetic Variants Toward Development of Personalized Medicine for Psoriasis Patients

Abstract: Psoriasis is multifactorial disease with complex genetic predisposition. Recent advances in genetics and genomics analyses have provided many insights into the relationship between specific genetic predisposition and the immunopathological mechanisms driving psoriasis manifestation. Novel approaches which utilize array-based genotyping technologies such as genome-wide association studies and bioinformatics tools for transcriptomics analysis have identified single nucleotide polymorphisms, genes and pathways th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 99 publications
0
10
0
Order By: Relevance
“…[16] We develop the line of argumentation that supports this hypothesis and argue that this treatment strategy expands and optimises therapeutic options for a personalised medicine approach in the future management of psoriasis. [17,18]…”
Section: (B) (C)mentioning
confidence: 99%
“…[16] We develop the line of argumentation that supports this hypothesis and argue that this treatment strategy expands and optimises therapeutic options for a personalised medicine approach in the future management of psoriasis. [17,18]…”
Section: (B) (C)mentioning
confidence: 99%
“…have been many exciting developments in precision medicine approaches for autoimmune diseases (32,33). Our study demonstrated, for the first time, that precision medicine could potentially be applied to the treatment of GD.…”
Section: Discussionmentioning
confidence: 59%
“…We believe that a similar approach will prove extremely useful to better understand the pathogenesis of psoriasis, making it easier to find new therapeutic strategies for this disease. Data obtained from large-scale studies combined with individual genetic profiles will be extremely useful to define prognosis and develop personalized medicine for psoriasis patients [139].…”
Section: Discussionmentioning
confidence: 99%